The emergence of the “jazz neighbourhood” of Kerameikos in recession Athens - Vavva, Georgia (The Greek Review of Social Research, 2020)
This paper maps the transformations related to the work practices of jazz venue owners and professional jazz musicians as a response to the crisis, and the ways in which these practices are spatialized in the area of Kerameikos in Athens, Greece. It is based on ethnographic fieldwork, conducted in 2015-2017 as part of my ethnomusicological doctoral research regarding the Athenian jazz scene in the post-2010 era. As I argue, the financescape disruption that occurred in 2010 triggered an impressive rise of small-scale musical performances and at the same time led to the prioritization of a globally-informed locality. In Kerameikos this process has been further assisted by the decelerating rhythms of gentrification, where shifts in the work practices of musicians and venue owners alike have brought together two concepts pertaining seemingly to contradicting social imaginaries, that of jazz and kafeneio, adding further to the emergent puzzling urban crisis-scape during this tumultuous period.